WISATA RELIGIUS DITINJAU KEMBALI: PERAN PERSEPSI DAN MOTIVASI DALAM KEMBALI KE ASTANA GIRIBANGUN - Yuliar, Ade; Bunga Ladesta Azhari (JURNAL KEPARIWISATAAN, 2026)
Religious tourism has become a growing phenomenon, with many communities making it a regular activity on a weekly, monthly, or annual basis. One prominent religious destination is Astana Giribangun in Karanganyar, the burial site of Indonesia's second president, Soeharto. This study employs a quantitative method using purposive sampling and Slovin's formula, resulting in 102 respondents. Data were collected through questionnaires. The results reveal that (1) tourist perception significantly and positively influences revisit intention, (2) travel motivation also has a significant and positive effect on revisit intention, and (3) both variables together account for 75.8% of the variance in revisit intention, with the remaining 24.2% influenced by other factors.